Flower-like CuS/graphene oxide with photothermal and enhanced photocatalytic effect for rapid bacteria-killing using visible light - Lv, Rui; Liang, Yan-Qin; Li, Zhao-Yang; Zhu, Sheng-Li; Cui, Zhen-Duo; Wu, Shui-Lin (Rare metals, 2022)
Pathogenic bacteria have been threatening the daily life of human beings. More effective methods without causing drug-resistance of bacteria need to be developed to fight against these pathogens. Herein, flower-like CuS/graphene oxide (GO) hybrids have been successfully synthesized via simple one-pot hydrothermal process. GO worked as an excellent electron acceptor to transport the photogenerated electrons from CuS, which can suppress the recombination of hole–electron pairs efficiently, thus enhancing the photocatalytic property. In addition, the morphology of CuS and GO with high specific surface area and the increased defect in GO also improved photocatalytic performance of the hybrid. Owing to the synergy of photothermal, enhanced photocatalytic effect and released Cu ions, CuS/GO exhibited outstanding antibacterial efficacy under visible light irradiation for 15 min. Additionally, the hybrid showed great biocompatibility to L929 cell. Hence, the synthesized CuS/GO would be a promising antibacterial material for daily life including rapid water disinfection and wounds sterilization. Graphic abstract